التدريبات اللغوية في تعليم اللغة العربية (دراسة وصفية تحليلية على كتاب "العربية بين يديك"): Linguistic Exercises in Teaching Arabic (Descriptive Study of Analysis of the Book of al-Arabiyah Baina Yadaika) - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2023)
This study aims to describe and analyze linguistic exercises in teaching Arabic in the book al-Arabiyyah Baina Yadaika. This type of research is a qualitative descriptive research using the library method by analyzing the textbook “al-Arabiyyah Baina Yadaika by looking for references in collecting data. The results of this study indicate that language exercises in teaching Arabic in the book al-Arabiyyah Baina Yadaika is a book that excels in presenting varied and intensive language exercises using Arabic without any instructional language, namely there are three main language exercises , as follows: first, al-Tadribāt al-Aliyyah, namely exercises that aim to make students accustomed to using language with repetition and imitation exercises; second, Tadribāt al-Ma'na, which is an exercise that aims to train students to be able to understand dialogue or reading texts with correct understanding through questions and answers based on the text; and third, al-Tadribat al-Itishaliyyah, which is an exercise that aims to familiarize students with direct communication by giving free questions that are not bound by text.